ATTITUDE OF MEDICAL STUDENTS TO BODY DONATION IN THE NATIONAL UNIVERSITY OF CORDOBA - ARGENTINA. Actitud de los estudiantes de Medicina en relación a la donación de cuerpos en la Universidad Nacional de Córdoba - Argentina - Susana Norma N. Biasutto; Marcos A. Spinelli; Diego M. Weigandt; Maria V. Mora; Atilio J. Bertocchi Valle; Ramiro A. A. Vargas; Isaias E. Molina Vargas; Oscar P. David; Daniel Urrutia (Asociación Argentina de Anatomía Clínica, 2019)
Corpses for teaching and research in Anatomy are fundamental, even having high developed technological resources. Although the National University of Cordoba is receiving bodies by donation, the quantity is very scarce and it barely allows the pre-graduate teaching activities, using prosected specimens for practical activities. It is essential to develop a donation program to increase body supply. The objective of the present study is to obtain data about the attitude of Medicine students in relation to body procurement and donation. We collected demographic data to provided a framework for analysis and specific data on organ and body donation. Samples from students of each and all years of the career were considered. For the 97% of the students cadavers were very important to study Anatomy. Most of the total students (94%) should be willing to donate their organs for transplantation, 84% were interested in getting more information on body donation, 42% should donate their own body and 75% could participate in procurement actions. Women were more willing to donate their organs than men, while men were more willing to donate their own bodies. Students who did not profess any religion had better attitude to donation. Medicine students from the National University of Cordoba have evidenced an important commitment to donation not only of organs but also of whole body because they recognize their importance, care future generations and have high values like altruism and solidarity.   La utilización de cuerpos humanos para docencia e investigación en el pre y posgrado resultan imprescindibles en Anatomía, aún disponiendo de tecnología de avanzada. Si bien la Universidad Nacional de Córdoba está recibiendo cuerpos por donación, la cantidad es muy escasa y apenas permite desarrollar las actividades docentes de pre-grado, usando preparados disecados para las actividades prácticas. Resulta imprescindible desarrollar un programa de donación para incrementar la provisión de cuerpos. El presente estudio pretende obtener datos que permitan conocer la actitud de los estudiantes de Medicina en relación a la procuración y donación de cuerpos. Se recabaron datos demográficos que brindaron un marco para el análisis y datos específicos sobre donación de órganos para trasplante y de cuerpos. Se consideraron muestras de alumnos correspondientes a todos los años de la carrera. Para el 97% los cuerpos son importantes para aprender Anatomía. El 94% donaría sus órganos para trasplante, al 84% le interesaría disponer de más información, el 42% donaría su propio cuerpo y el 75% participaría en un programa de procuración. Las mujeres tuvieron mayor disposición a la donación de órganos para trasplante, mientras que los varones hacia la donación de cuerpos (BD) para docencia e investigación. Quienes no profesan ninguna religión fueron más positivos hacia la BD. Los estudiantes de Medicina evidenciaron un importante compromiso con la donación tanto para trasplante como de cuerpos completos, porque reconocen la importancia de ambos, se preocupan por las generaciones futuras y cuentan con valores como el altruismo y la solidaridad.